Metal-Oxide-Semiconductor Characteristics of Zr-Oxynitride Thin Film on 4H-SiC Substrate - Wong, Yew Hoong; Cheong, K.Y. (Electrochemical Society, 2012)
Sputtered Zr on 4H-SiC substrate and followed by simultaneous oxidation and nitridation in nitrous oxide ambient at various temperatures (400–900°C) for 15 min have been systematically investigated. The structural and electrical properties of the samples were evaluated. Energy-filtered transmission electron micrographs demonstrated that an interfacial layer (IL) of 1.44 to 4.20 nm had been formed in between a bulk oxide of 14.63 to 18.53 nm and the SiC substrate, depending on the temperature. The calculated activation energies for the bulk oxide, which was Zr-oxynitride, IL, and total oxide growth were −0.0335 eV, 0.1543 eV, and −0.0078 eV, respectively. Supportive results were obtained from X-ray diffractometer, Raman spectrometer, and atomic force microscope. The electrical results revealed that 500°C oxidized/nitrided sample has demonstrated the highest breakdown field and reliability. This was attributed to the lowest total interface trap, effective oxide charge, and highest barrier height between conduction band edge of oxynitride and semiconductor.